The Effect of Principal Competence and Educational Facilities on Education Quality Mediated by Teacher Job Satisfaction in State Elementary Schools in Pandeglang Regency - Minarti Agustina; Bambang Herawan Hayadi; Minhatul Ma’arif (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the direct and indirect effects of principal managerial competence and educational facilities on the quality of education in public elementary schools (SDN) in Pandeglang Regency, with teacher job satisfaction serving as a mediating variable. Research Method: A quantitative approach with an explanatory survey design was employed in this research. Data were gathered from 125 teachers at A-accredited public elementary schools in Pandeglang Regency, Banten Province, using a closed-ended questionnaire with a 1–5 Likert scale that passed validity and reliability tests. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software version 4, alongside Microsoft Excel for initial data processing. Results: All seven hypothesized paths were proven significant at . Principal managerial competence and educational facilities each had a strong effect on teacher job satisfaction ( and , respectively), while their direct effects on education quality were more moderate ( and ). Teacher job satisfaction positively affected education quality () and was proven to partially mediate the effects of both exogenous variables ( and ). Overall, the model explained 90.1% of the variance in teacher job satisfaction and 88.3% of the variance in education quality. Conclusion: The quality of education in public elementary schools in Pandeglang Regency is influenced more indirectly through the enhancement of teacher job satisfaction than purely through structural-administrative measures. Therefore, quality improvement policies should be holistic, taking into account the psychological well-being of teachers. Limitations: This study is limited to teachers in A-accredited schools within a single regency using a cross-sectional design; thus, generalizations to other education levels or different regional contexts should be made with caution. Contribution: These findings enrich the literature on elementary education management by emphasizing teacher job satisfaction as a crucial bridge between managerial leadership, facility availability, and education quality. This study serves as a valuable reference for local education departments, school principals, and educational researchers.This study aims to analyze the direct and indirect effects of principal managerial competence and educational facilities on the quality of education in public elementary schools (SDN) in Pandeglang Regency, with teacher job satisfaction serving as a mediating variable. Research Method: A quantitative approach with an explanatory survey design was employed in this research. Data were gathered from 125 teachers at A-accredited public elementary schools in Pandeglang Regency, Banten Province, using a closed-ended questionnaire with a 1–5 Likert scale that passed validity and reliability tests. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software version 4, alongside Microsoft Excel for initial data processing. Results: All seven hypothesized paths were proven significant at . Principal managerial competence and educational facilities each had a strong effect on teacher job satisfaction ( and , respectively), while their direct effects on education quality were more moderate ( and ). Teacher job satisfaction positively affected education quality () and was proven to partially mediate the effects of both exogenous variables ( and ). Overall, the model explained 90.1% of the variance in teacher job satisfaction and 88.3% of the variance in education quality. Conclusion: The quality of education in public elementary schools in Pandeglang Regency is influenced more indirectly through the enhancement of teacher job satisfaction than purely through structural-administrative measures. Therefore, quality improvement policies should be holistic, taking into account the psychological well-being of teachers. Limitations: This study is limited to teachers in A-accredited schools within a single regency using a cross-sectional design; thus, generalizations to other education levels or different regional contexts should be made with caution. Contribution: These findings enrich the literature on elementary education management by emphasizing teacher job satisfaction as a crucial bridge between managerial leadership, facility availability, and education quality. This study serves as a valuable reference for local education departments, school principals, and educational researchers.